PENERAPAN PEMBUKTIAN TERBALIK DALAM PERKARA GRATIFIKASI - Lestari Victoria Sinaga; Alvi Syahrin; Muhammad Hamdan; Dedi Harianto (Universitas Sumatera Utara, 2016)
ABSTRACT Based on the results of this study, the idea of the principle of reversal of the burden of proof imposed a total and absolute terms has been accepted since the Act No. 3 of 1971 with the formulation of the defendant can prove that he is not corrupt, but the burden of proof of alleged corruption in the hands of the public prosecutor. Legislation is only put evidence as a “shift” only instead of “reversal” burden of proof, so that the term in Law No. 31 of 1999 on a system of proof is reversal of the burden of proof is limited and balanced. Implementation of the system of proof in a criminal act of gift giving No. 98 / Pid.Sus / Tpk / 2013 Bandung District Court on behalf of Billy Sutejo that the use of money to establish a Building Permit is used for its own sake. The judge in imposing the acquittal to the accused is the misinterpretation of article 12B, paragraph 1, letter b clarified that the corruption is a formal offense, enough with the fulfillment of the elements of the act does not have to exist as a result. This has become less conscientious judge in making a decision. Excess application of reversed burden of proof is accused human rights protected in front of the court in terms of evidence. Description defendant help ensure public prosecutor in the trial. While the weakness is first of proof that an article that is not in the bedroom but the law can not be applied into practice. Keywords: Reversal of the Burden of Proof, Gratification, Corruption Criminal Act